PROBLEMS IN TRANSLATING IDIOMS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article we will talk about idioms, some of their types and some problems in translation. Idioms are such combinations that their translation consists of several stages and is considered a very complicated process. Therefore, translating idioms in the field of linguistics requires great skill and time. Many people make mistakes when translating idioms, and they sometimes lead to irreparable mistakes. In this article, we will talk about the mistakes that many people make in translation and how to avoid them.